2016
DOI: 10.1177/0267659116656774
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care platelet function testing to predict blood loss after coronary artery bypass grafting surgery: a prospective observational pilot study

Abstract: This pilot study shows that preoperative multiplate testing may be a better predictor of platelet dysfunction and the resultant blood loss following cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The effects of CPB on platelet function were studied by Ellis and associates in 2016 [22]; the authors measured platelet function with TEG, TEG-PM, and MEA before and after CPB. All the tests showed a decreased platelet function after CPB; however, TEG and TEG-PM values did not predict bleeding after cardiac surgery.…”
Section: Modified Vet: Teg Platelet Mappingmentioning
confidence: 99%
“…The effects of CPB on platelet function were studied by Ellis and associates in 2016 [22]; the authors measured platelet function with TEG, TEG-PM, and MEA before and after CPB. All the tests showed a decreased platelet function after CPB; however, TEG and TEG-PM values did not predict bleeding after cardiac surgery.…”
Section: Modified Vet: Teg Platelet Mappingmentioning
confidence: 99%
“…In contemporary literature, the frequency of significant postoperative bleeding ranges from 5% to 50% 2 . The origin of the hemostatic disturbances after cardiac surgery is multifactorial—the effect of the heart‐lung machine (CPB) on platelet function, activated coagulation cascade, heparin‐induced coagulopathy, and fibrinolysis 3 . Postoperative morbidity caused by excessive bleeding is also a consequence of higher blood transfusion rate, as well as mechanisms that are not transfusion‐related 4 …”
Section: Introductionmentioning
confidence: 99%
“…A pilot study performed at our institute showed a superior predictive ability of the Multiplate to guide platelet transfusion as compared with Platelet Mapping. 17 Following this, Multiplate testing has become the standard of monitoring preoperative drug-induced platelet dysfunction at our institute. The Multiplate platelet function analyzer incorporates the use of impedance aggregometry to detect platelet function.…”
Section: Methodsmentioning
confidence: 99%